Caracterização paisagística dos Parques Nacionais do Iguaçu e Iguazu - Colpani, Juraci (2017)
Parque Nacional do Iguaçu – PNI (Brazil) and Parque Nacional Iguazú – PNI (Argentina) are considered important humanitarian monuments distinguished as one of the seven world wonders. Both parks are conterminous and share a geological, biodiverse and common cultural history. However, the landscapes of these parks are presented in an unilateral way. Most of the times the patrimony divulgation process disconsiders the landscaping continuities and the conterminous diversity, this way most of the visitors go to the Iguassu Falls only with a partial vision of the complex system, which links geographically both parks, PNI (BR) and PNI (ARG). When considering the relevance of understanding these national parks as a single patrimony, the present study is designated to integrate the informations about the natural and social aspects of both parks, in order to offer ways of enhancing the knowledge dissemination in an integrated manner. In order to understand how the landscape of these national parks structured itself over time and space, the biodiversity and geodiversity chacterization was carried out together with the geographical – historical occupation, which comprises the established relation of the nature – society plan. Monteiro‟s proposal (2001) is the main guiding of the research, which considers the landscape an open and complete system where the abiotic, biotic, anthropic and socialcultural elements correspond to each other. The natural energy flows analyzed were geological, geomorphological, hydrological, pedological and biological. The anthropo social flows were the historical context, the European and Guarani context the nationalization and internationalization of PNI (Brazil) and PNI (Argentina) patrimony. The theoretical basis of Schama (1995), Sauer (1998), Diegues (2001) e Claval (2002, 2014) were used to help on the cultural ladscape grounding. With the database acquired, thematic maps were elaborated and united into a cartogram, which facilitated the presentation of geophysics chacteristics of the environment and cultural influence.This mosaic composition eased the elements‟ exhibition which are part of the singleness of the landscapes from both parks, PNI (Bra) and PNI(Arg). In order to present the integrated interpretation of the described informations in the cartogram,it was created an analysis chart about the interrelationships of landscaping system from both parks, which enabled the distinct potential validation of each park.